Association between smoking and the clinical status of adult patients with moderate-severe atopic dermatitis in the China Atopic Dermatitis Registry (ChinaSTAD): a cross-sectional study - Yingzhe Yu; Lu Cao; Xin Fan; Lingyi Lu; Sihan Wang; Jianzhong Zhang; Bingjiang Lin (Frontiers in Medicine, 2026)
Background Atopic dermatitis (AD) is a common inflammatory skin disease influenced by multiple factors such as genetic, environmental and lifestyle factors. This study explored the association between smoking and AD. Methods The China Atopic Dermatitis Registry (ChinaSTAD) is a nationwide observational registry of patients with moderate to severe AD in China. We conducted a cross-sectional analysis of adult patients enrolled from July 2021 to April 2023 across 26 provinces. Patients were categorized as ever-smokers or non-smokers based on smoking history. Propensity scores were estimated using demographic and socioeconomic covariates, with 1:1 nearest neighbor matching applied. Associations between smoking status and clinical/patient-reported outcomes were evaluated using linear regression models with robust standard errors. Sensitivity analyses were performed by comparing results from unmatched, matched and doubly robust approaches. Results After propensity scores matching, baseline characteristics were well-balanced. In the doubly robust analyses, smoking was associated with greater body surface area (BSA) values (adjusted mean difference 2.29, 95% CI 0.22–4.36), and showed a weak association with Patient Oriented Eczema Measure (POEM) scores (adjusted mean difference 0.59, 95% CI −0.00 to 1.19). In contrast, no clear association was found between smoking and other patient-reported outcomes and quality of life indicators. Sensitivity analysis showed that effect estimates varied across strategies and were generally attenuated after doubly robust adjustment. Conclusion In this study, smoking was associated with BSA, but with weak or no association with disease severity, clinical phenotype or quality of life scores. Further prospective studies are required to clarify the relationship between smoking and AD.